HUBUNGAN KEKUATAN OTOT LENGAN, KEKUATAN OTOT PINGGANG DAN POWER OTOT TUNGKAI TERHADAP KECEPATAN HASIL BANTINGAN TEKNIK SEOI NAGE PADA ATLET PUTRA DI PADEPOKAN SEISHIN JUDOKA CLUB USIA 16-20 TAHUN - Surya Pratama, Aldo; Joan Siswoyo; Alifia Ramadhina Putri; Fransiskus Nurseto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the relationship between arm muscle strength, hip muscle strength, and leg muscle power with the speed of Seoi Nage throwing performance among male athletes aged 16–20 years at the Seishin Judoka Club training center. The research applied a quantitative approach using a correlational method. The sample consisted of 20 athletes selected through a total sampling technique. The instruments included arm muscle strength tests, hip muscle strength tests, leg muscle power tests, and a Seoi Nage throwing speed test. The data were analyzed using Pearson Product Moment correlation and multiple regression analysis with the assistance of SPSS at a significance level of 0.05. The results indicated that (1) there was a significant relationship between arm muscle strength and Seoi Nage throwing speed (r = 0.601 > r-table = 0.444), (2) hip muscle strength also showed a significant relationship (r = 0.640 > r-table = 0.444), and (3) leg muscle power had a significant relationship with throwing speed (r = 0.700 > r-table = 0.444). Simultaneously, the three variables showed a significant relationship with Fcount = 7.401 > Ftable = 3.239 and contributed 58.1%. In conclusion, arm muscle strength, hip muscle strength, and leg muscle power play an important role in improving the speed of Seoi Nage throwing performance in judo athletes.